Bailing Out Expectations and Health Expenditure in Italy - Massimo Bordignon; Gilberto Turati (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this paper we propose a simple model of bailing out that closely describes the intergovernmental relationships between the Central government and the regional governments in the Italian public health care sector. The theoretical model suggests that bail out expectations by regions can be thought as the missing variable emphasised by Culyer (1988) in empirical models explaining health expenditure. We test this prediction by using data on regional health expenditure during the years 1990-1999. We show that financing by regions is influenced by political variables that capture changes in bail out expectations. This expected funding has a positive relationship with expenditure, even when Central government decreased financing to regions. Moreover, the alignment effect shows that friendly regional governments receive more money and support Central government by reducing expenditure.
Keywords: 330; health care expenditure; intergovernmental relationships